2020
DOI: 10.1186/s12889-020-09619-z
|View full text |Cite
|
Sign up to set email alerts
|

Never and under cervical cancer screening in Switzerland and Belgium: trends and inequalities

Abstract: Background Research on inequalities in cervical cancer screening (CCS) participation has overlooked the distinction between ‘never-’ and ‘under-screeners’ while different socioeconomic and demographic determinants may underlie ‘non-’ and ‘under-’ screening participation. This study examines socioeconomic and demographic inequalities in never and under CCS participation. We compare cross-national prevalence and trends among these two groups in Switzerland and Belgium, two countries with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
4
24
0
1
Order By: Relevance
“…Also, previous studies support the notion that preventive screenings are more prevalent in higher SES groups [31,32]. Our nding that higher SES groups higher odds for dentists and dental hygienist visits con rms a wellknown phenomenon [11,12,33,34]. Besides the fact that visits to dentists and dental hygienists are usually not covered by health insurance and thus reinforcing income inequalities in utilization, similar arguments can be used to explain the differences in utilization as other preventive medical treatments.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Also, previous studies support the notion that preventive screenings are more prevalent in higher SES groups [31,32]. Our nding that higher SES groups higher odds for dentists and dental hygienist visits con rms a wellknown phenomenon [11,12,33,34]. Besides the fact that visits to dentists and dental hygienists are usually not covered by health insurance and thus reinforcing income inequalities in utilization, similar arguments can be used to explain the differences in utilization as other preventive medical treatments.…”
Section: Discussionsupporting
confidence: 83%
“…Despite the fact that Switzerland is a high-income country with universal health coverage and a highly developed social welfare system, social inequalities in health service utilization were also observed for the Swiss context [6][7][8][9][10][11][12]. Studies report different patterns of utilization across SES groups [6-8, [10][11][12], but also provide evidence for income inequalities in unmet health care needs [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic inequalities in cervical and breast cancer screening tests were evidenced to persist over time and across European countries ( Damiani et al, 2015 ; Jolidon et al, 2020 ; Sabates & Feinstein, 2006 ; Willems & Bracke, 2018 ; Wubker, 2014 ). Nevertheless, the only country-level factors research has addressed are the cancer screening programmes ( Palencia et al, 2010 ; Walsh et al, 2011 ; Willems & Bracke, 2018 ) and macrolevel gender inequality ( Willems et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other factors include, a history of multiple sexual partners, HIV-positive status and women's social interactions [9,10,11,12,13,14,15,16,17,18]. These studies showed that women who were older, resided in urban areas, and were more educated and wealthier were screened more often than younger, rural residents, uneducated, and poor women, with a few exceptions [9,19,20,21,22]. However, these studies did not estimate the magnitude of inequalities and their combined impact on cervical pre-cancer screening.…”
mentioning
confidence: 99%